2003
DOI: 10.1093/hmg/ddg104
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 haplotype associated with increased risk of hepatocellular carcinoma

Abstract: Interleukin 10 (IL10) is a powerful Th-2 cell cytokine produced by lymphoid cells that exerts its functions by inhibiting macrophage/monocyte and T-cell lymphocyte replication and secretion of inflammatory cytokines (IL1, TNFA, TGFB, IL6, IL8 and IL12). Genetic association analysis of a well-characterized HBV cohort revealed that one of IL10 haplotypes, IL10-ht2, was strongly associated with hepatocellular carcinoma (HCC) occurrence in gene dose-dependent manner. The frequency of susceptible IL10-ht2 was much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
5
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 24 publications
10
97
5
2
Order By: Relevance
“…Several studies have reported an association between cytokine SNPs and HCC occurrence [10,22]. Shin et al [10] reported that IL10-ht2 (high IL-10 secretor phenotype) accelerates the progression of chronic HBV infection, especially the development of HCC in the Korean population, although the exact functional mechanisms of HCC occurrence were not clearly explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported an association between cytokine SNPs and HCC occurrence [10,22]. Shin et al [10] reported that IL10-ht2 (high IL-10 secretor phenotype) accelerates the progression of chronic HBV infection, especially the development of HCC in the Korean population, although the exact functional mechanisms of HCC occurrence were not clearly explained.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that cytokine polymorphisms are associated with the natural history of HBV infections in Korea [9,10]. Our research group has investigated host genetic factors that are associated with HBV infection outcomes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The variants (À1082A4G, À592A4C and IL10-ht2 [A-C-C-T]) in the IL10 (interleukin 10) gene were associated with age of HCC occurrence among the CC group. 5 In addition, a promoter polymorphism in the HDAC10 (histone deacetylase 10) gene, À589C4T was also associated with the onset age of HCC. 3 CCND2 is known to be involved in immune responses.…”
Section: ) the Ht1 [T-c-t-a-t]mentioning
confidence: 99%
“…3 In addition to that, several previous studies have also reported associations between genetic polymorphisms and the risk of HCC and/or clearance of HBV. [3][4][5][6][7] D-type cyclins are the main integral mediators associating the extracellular signaling environment with cell-cycle progression. They are divided into three subtypes: cyclin D1, D2 and D3.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The IL10 gene has been implicated in the response to a number of diseases such as hepatitis B, pulmonary tuberculosis, herpes zoster, cutaneous malignant melanoma, hepatocellular carcinoma fibrosis, gastric carcinoma, squamous cell carcinoma, inflammatory bowel disease, and HIV. [26][27][28][29][30][31][32][33][34] The genetic neighbors of IL10 consisting of IL19, IL20, and IL24 also modulate the TH1 and TH2 response, suggesting that these recently discovered loci could also be important in HCV clearance. 35 A number of studies have examined the IL10 promoter region SNPs and their associations with HCV susceptibility as well as resistance to antiviral therapy.…”
Section: Introductionmentioning
confidence: 99%